Outcomes following transoral robotic surgery: Supraglottic laryngectomy12. (24th September 2012) - Mendelsohn, Abie H.; Remacle, Marc; Van Der Vorst, Sebastien; Bachy, Vincent; Lawson, Georges
Abstract Objectives/Hypothesis: To describe a single center outcomes following transoral robotic surgery for supraglottic laryngectomy (TORS–SL). Study Design: Prospective data collection. Methods: Patient records receiving TORS–SL for squamous cell carcinoma (SCCA) with at least 12 months follow‐up fit inclusion for this study. Two patients with previous SCCA were excluded. Results: 18 patients (14 male, 4 female) were included in the study, having a mean follow‐up time of 28.1 months (SD = 12.1). All patients had negative margins confirmed on final pathology. Nine (50%) patients received postoperative chemoradiation therapy for advanced neck disease. No (0%) patients received tracheostomy or gastrostomy tubes. There were no (0%) local recurrences, and three (16.7%) regional recurrences. Five (27.8%) patients experienced temporary postoperative complications. Overall 2‐year outcomes reached 83%, 100%, and 89% for locoregional control, disease‐specific survival, and overall survival respectively. Conclusions: Initial outcomes for TORS–SL are encouraging and are comparable to previously described treatment modalities. Larger studies are encouraged. Laryngoscope, 2013